Evaluation of losses in maritime gearboxes. (November 2016) - Godjevac, Milinko; Drijver, Joost; de Vries, Leo; Stapersma, Douwe
Gearboxes are a necessary part of almost any propulsion train and their percentual losses are usually assumed to be small and constant. However, in low-load and part-load conditions, gearbox losses may be significant. With the current trend of slow steaming, the performance of gearboxes is once again in focus. In order to estimate the performance of maritime gearboxes, an evaluation of losses was done using a thermal network. The analysis was done for a standard double-input single-output maritime gearbox and over the entire range of torque and revolutions per minute. Results indicate that the transmission losses are not negligible in low-load condition; in fact they may as high as 10% of delivered power. Further results show that the maximum temperature in the teeth contact can reach 70 °C but this might be an overestimate. Finally, using the investigated thermal network models, a simplified model of transmission losses is proposed together with the fit coefficients for the torque and revolutions per minute.